Synthesis and biological evaluation of thiazolidinedione derivatives with high ligand efficiency to P. aeruginosa PhzS - Thamires Quadros Froes; Bianca Trindade Chaves; Marina Sena Mendes; Rafael Matos Ximenes; Ivanildo Mangueira da Silva; Priscila Brandão Gomes da Silva; Julianna Ferreira Cavalcanti de Albuquerque; Marcelo Santos Castilho (Taylor & Francis Group, 2021)
The thiazolidinone ring is found in compounds that have widespan biology activity and there is mechanism-based evidence that compounds bearing this moiety inhibit P. aeruginosa PhzS (PaPzhS), a key enzyme in the biosynthesis of the virulence factor named pyocyanin. Ten novel thiazolidinone derivatives were synthesised and screened against PaPhzS, using two orthogonal assays. The biological results provided by these and 28 other compounds, whose synthesis had been described, suggest that the dihydroquinazoline ring, found in the previous hit (A- Kd = 18 µM and LE = 0.20), is not required for PaPzhS inhibition, but unsubstituted nitrogen at the thiazolidinone ring is. The molecular simplification approach, pursued in this work, afforded an optimised lead compound (13- 5-(2,4-dimethoxyphenyl)thiazolidine-2,4-dione) with 10-fold improvement in affinity (Kd= 1.68 µM) and more than 100% increase in LE (0.45), which follows the same inhibition mode as the original hit compound (competitive to NADH).Executive summary PhzS is a key enzyme in the pyocyanin biosynthesis pathway in P. aeruginosa. Orthogonal assays (TSA and FITC) show that fragment-like thiazolidinedione derivatives bind to PaPhzS with one-digit micromolar affinity. Fragment-like thiazolidinedione derivatives bind to the cofactor (NADH) binding site in PaPhzS. The molecular simplification optimised the ligand efficiency and affinity of the lead compound.